Cameroon : 2011: Article IV Consultation: Staff Report; Debt Sustainability Analysis; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, Cameroon's economic recovery, low inflation, and positive economic prospects have been ascribed. Efforts to improve non-oil revenue by broadening the tax base, streamlining exemptions, and increasing the efficiency of tax and customs administration are outlined. The need to rebuild fiscal buffers, strengthen the budget execution process, and accelerate efforts to operationalize the medium-term expenditure framework are emphasized. The importance of redoubling efforts to address the severe infrastructure gap and improve the business climate and competitiveness are also provided.